การจัดการความรู้เพื่อพัฒนาการออกแบบผลิตภัณฑ์และวิเคราะห์ศักยภาพธุรกิจชุมชน อำเภอดอยสะเก็ด จังหวัดเชียงใหม่ - โสมดี, อัญชลี (Community and Social Development Journal, 2012)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความต้องการชุมชนเกี่ยวกับการพัฒนาผลิตภัณฑ์และศักยภาพชุมชนการศึกษารูปแบบผลิตภัณฑ์ในต้านแนวความคิด กลวิธีการออกแบบ ขั้นตอนการผลิต ภูมิปัญญาชาวบ้าน ทัศนคติสภาพแวดล้อม ต้นทุนทางธรรมชาติที่ส่งผลกระทบต,อรูปแบบผลิตภัณฑ์รวมไปถึงการจัดการความรู้ต้านการออกแบบพัฒนาสร้างสรรค์ผลิตภัณฑ์ชุมชนโดยผู้เชี่ยวชาญต้านการออกแบบ และการจัดการความรู้เพื่อการวิเคราะห์ศักยภาพต้านการจัดการ การตลาด การผลิต และการดำเนินงานเกี่ยวกับธรกิจชุมชนบนพื้นฐานปรัชญาเศรษฐกิจพอเพียงของพระบาทสมเด็จพระเจ้าอยู่หัวเพื่อการพัฒนาชีวิตและเศรษฐกิจชจุมชนให้ยั่งยืน ด้วยกระบวนการจัดการความรฆํ้และวิธีวิจัยเชิงคุณภาพกับการวิจัยเชิงปฏิบ้ติการแบบมีส่วนร่วม โดยมีกลุ่มตัวอย่างการศึกษา ได้แก่ กลุ่มผู้ประกอบการในพื้นที่อำเภอดอยสะเก็ด จังหวัดเชียงใหม่ จำนวน 46 กลุ่ม จาก 14 ตำบล ผลจากการวิจัย พบว่า กลุ่มธุรกิจชุมชนมีความต้องการที่จะพัฒนาผลิตภัณฑ์ และศักยภาพในกลุ่มตนเองเพื่อการพัฒนาความรู้ ความเชี่ยวชาญในการผลิต การออกแบบผลิตภัณฑ์ การศึกษารูปแบบผลิตภัณฑ์และกลวิธีการออกแบบกลุ่มธุรกิจชุมชนมีการออกแบบพัฒนาผลิตภัณฑ์เป็นการร่วมกันแสดงความคิดเห็นโดยมีประธานกลุ่มเป็นผู้ควบคุมดูแลการผลิตการออกแบบ ส่วนขั้นตอนการผลิตเป็นการก่ายทอดกลวิธีปฏิบัติงานจากประธานกลุ่มไปสู่สมาชิกภายในกลุ่ม หลังจากนั้นสมาชิกภายในกลุ่มจะเป็นผู้ก่ายทอดให้แก่สมาชิกคนอื่นๆ ต่อไป การจัดการความรู้ต้านการออกแบบพัฒนาสร้างสรรค์ผลิตภัณฑ์ชุมชน และศักยภาพต้านการจัดการ การตลาด การผลิต และการดำเนินงานต้านธุรกิจชุมชน พบว่า จากการที่กลุ่มธุรกิจชุมชนไต้รับการบริการความรู้ต้านต่างๆ โดยคณะผู้วิจัยวิทยากร รวมถึงจัดเวทีแลกเปลี่ยนเรียนรู้ ส่งผลให้ธุรกิจชุมชนมีความพร้อมในการพัฒนาตนเอง และการปฏิบัติงานให้มีประสิทธิภาพมากยิ่งขึ้น อีกทั้งยังนำหลักปรัชญาเศรษฐกิจพอเพียงมาประยกต็ใช้ในการจัดการธรกิจของตน เพื่อการดำเนินงานพัฒนาชีวิตและเศรษฐกิจชุมชนให้ยั่งยืนต่อไป Knowledge Management Process to Development Product Designs and Analysis Community Business Potentiality, Doi Saket District, Chiang Mai Province The purposes of this research aim to study the community’s need about product and community’s potential development, to study product pattern concerning with concept, design methods, manufacturing procedure, local wisdom, attitude, environment, natural capital affecting to product pattern including knowledge management on community’s product development by design experts. Also, it is to provide the knowledge management to analyze the potential of marketing, manufacturing and community business operation on self-sufficiency economy basis by His Majesty the King Rama IX for sustainable life quality and community business development with knowledge management process and utilization of Qualitative Research and Participatory Action Research. The research sample groups are 46 groups from 14 sub-districts in Doi Saket district, Chiang Mai province. According to the study, it was found that the community needs to improve the products and potential within their group in order to develop knowledge and expertise in manufacturing and designing their further products. Also, for the study on product pattern and design method, the community business groups design and develop their products by giving opinion as the group president will be in charge of supervising the manufacturing and designing. On, manufacturing process, it is performed by instructing procedures from group president to members. After that, members will instruct to other members. On, community product knowledge management process and potential of management, marketing, manufacturing, and operating, it was found that after being instructed for variety of knowledge from researchers and lecturers including knowledge exchanging session, community business groups have become more prepared to improve themselves and to perform with better effectiveness. Also, they are able to apply self-sufficiency economy concept for their business, operations and community business for sustainability.